2017
DOI: 10.1002/admt.201700177
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Superparamagnetic Microparticles with an Electromagnetic Needle

Abstract: organisms. The manipulation of superparamagnetic microparticles, in particular, has a wide range of applications, including magnetic logic; [13] sorting and trapping of magnetically tagged proteins, [14] cells, [15] and microorganisms; [16] microfluidic mixing; [17] magnetoresistive biosensing; [18] immunoassays; [19] and lab-on-a-tube devices. [20] In principle, the manipulation methods of these microparticles can be cate gorized into two groups: batch and individual particle manipulation. In batch manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
0
31
0
1
Order By: Relevance
“…Much effort has been devoted to improving their behavior in extensive biomedical areas, including bioseparation, biosensor, medical imaging techniques, and therapy . For example, it is reported that after being bonded to specifically designed polymers or biological molecules and assembling into particular structures, the ability of ferromagnetic particles to capture and separate targets could be significantly improved, thus extremely enhancing the bioseparation and biosensing efficiency . In addition, by properly modifying their surface or using them to form magnetically responsive microspheres, the half‐life period could be noticeably elongated.…”
Section: Ferrofluid‐based Detection Diagnosis and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Much effort has been devoted to improving their behavior in extensive biomedical areas, including bioseparation, biosensor, medical imaging techniques, and therapy . For example, it is reported that after being bonded to specifically designed polymers or biological molecules and assembling into particular structures, the ability of ferromagnetic particles to capture and separate targets could be significantly improved, thus extremely enhancing the bioseparation and biosensing efficiency . In addition, by properly modifying their surface or using them to form magnetically responsive microspheres, the half‐life period could be noticeably elongated.…”
Section: Ferrofluid‐based Detection Diagnosis and Therapymentioning
confidence: 99%
“…[33,172] For example, it is reported that after being bonded to specifically designed polymers or biological molecules and assembling into particular structures, the ability of ferromagnetic particles to capture and separate targets could be significantly improved, thus extremely enhancing the bioseparation [173][174][175] and biosensing efficiency. [18,[176][177][178] In addition, by properly modifying their surface or using them to form magnetically responsive microspheres, the half-life period could be noticeably elongated. Meanwhile, the uptake by macrophage cells could be greatly reduced and the accurate regional targeting could also be achieved, making the ferromagnetic particles applicable to MRI, [179,180] target drug delivery, [29,[181][182][183][184] and hyperthermia.…”
Section: Ferrofluid-based Detection Diagnosis and Therapymentioning
confidence: 99%
“…The particles manipulated by the EMN are subject to two different forces: i) the magnetic force, F m , which is a function of the distance between the particle and the needle tip, and ii) the drag force, F d , induced by motion in the fluid. These forces can be expressed as follows [36]:…”
Section: Concept Of the Non-contact Manipulationmentioning
confidence: 99%
“…The proposed method has been demonstrated in four cases: selective extraction, separation of two particles, independent manipulation of four particles and targeted delivery of two particles on two separate cells. This work is built upon our previous work on contact manipulation using electromagnetic needle [36].…”
Section: Introductionmentioning
confidence: 99%
“…Local actuation of single pillars with aspect ratio of 6.6 by an electromagnetic needle [18] was used to determine the deflection and the responsiveness of the magnetic pillars immersed in water. The electromagnetic needle is oriented at ≈45° at a fixed distance from the pillar and the tip of the needle is leveled with the pillar edge.…”
Section: Doi: 101002/marc201900522mentioning
confidence: 99%